The ‘Ecclesiarum Belgicarum Confessio’ and the Attempted ‘Calvinisation’ of the Orthodox Church under Patriarch Cyril Loukaris - Tsakirēs, Basileios (The journal of ecclesiastical history, 2012)
The Calvinistic Confession of Faith written by the patriarch of Constantinople, Cyril Loukaris, is considered to be the most important product and at the same time the manifesto of the attempted union of the Protestant and Orthodox Churches. Presenting evidence which has been neglected in previous research, this article aims to revise this communis opinio by demonstrating that the book that was actually meant to become the theological foundation for the envisaged union was in fact the Ecclesiarum Belgicarum Confessio, a bilingual (Latin and Greek) publication (1623, 1627, 1648) containing the Βelgic Confession, the Heidelberg Catechism and several canons of the Synod of Dordrecht.